Association of dyslipidemia with intakes of fruit and vegetables and the body fat content of adults clinically selected for a lifestyle modification program - Takahashi, Mauro Massao [UNESP]; De Oliveira, Erick Prado [UNESP]; Moreto, Fernando [UNESP]; Portero-McLellan, Kátia Cristina [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 2010)
To investigate the relationship of dyslipidemia with demographic distribution and patterns of body fat and dietary intakes. From a universe of adults clinically selected for a lifestyle modification program 979 subjects (409 males and 570 females, 52.2 ± 9.6 years) fulfilled the inclusion criteria. Overnight-fasting plasma was assayed (dry chemistry) for triglycerides (TG), total (TC) and HDL fraction of cholesterol given the non-HDL (n-HDL) fraction by the difference. Anthropometric assessment included body weight (kg), height (m), fat (bioelectrical impedance) and waist circumference (WC). Food intake was assessed by the 24-hour recall questionnaire and the food groups evaluated through recommendations from an adapted food pyramid. The chances of dyslipidemia from other variable changes were determined by logistic regression with p<0.05. Normal values of BMI and WC were protective against all dyslipidemia markers whereas only hypercholesterolemia was influenced by diet (meat intake >2 servings). Dietary intakes have protective effects against hypertriglyceridemia with whole grains, odds ratio (OR) 0.342 (CI 95%, 0.154-0.760), fruits >3 servings (OR 0.523, 0.290-0.941) and vegetables >4 servings (OR 0.360, 0.176-0.735). In general total body and abdominal adiposity influenced all dyslipidemia markers while dietary intake of fruits and vegetables protected against triglyceridemia.
Keywords: Body composition; Dietary components; Dyslipidemia